Evidence that increased 5-HT release evokes region-specific effects on blood-oxygenation level-dependent functional magnetic resonance imaging responses in the rat brain. - Preece, M; Taylor, M; Raley, J; Blamire, A; Sharp, T; Sibson, N (2009)
This study aimed to determine the potential of in vivo functional magnetic resonance imaging (fMRI) methods as a non-invasive means of detecting effects of increased 5-HT release in brain. Changes in blood-oxygenation level-dependent (BOLD) contrast induced by administration of the 5-HT-releasing agent, fenfluramine, were measured in selected brain regions of halothane-anesthetized rats. Initial immunohistochemical measurements of the marker of neural activation, Fos, confirmed that in halothane-anesthetized rats fenfluramine (10 mg/kg i.v.) evoked cellular responses in cortical regions which were attenuated by pre-treatment with the 5-HT synthesis inhibitor p-chlorophenylalanine (300 mg/kg i.p. once daily for 2 days). Fenfluramine-induced Fos was demonstrated in numerous glutamatergic pyramidal neurons (Fos/excitatory amino acid carrier 1 (EAAC1) co-labeled), but also a small number of GABA interneurons (Fos/glutamic acid decarboxylase (GAD)(67) colabeled). Fenfluramine (10 mg/kg i.v.) evoked changes in BOLD signal intensity in a number of cortical and sub-cortical regions with the greatest effects being observed in the nucleus accumbens (-13.0%+/-2.7%), prefrontal cortex (-10.1%+/-3.2%) and motor cortex (+2.3%+/-1.0%). Pre-treatment with p-chlorophenylalanine, significantly attenuated the response to fenfluramine (10 mg/kg i.v.) in all regions with the exception of the motor cortex which showed a trend. These experiments demonstrate that increased 5-HT release evokes region-specific changes in the BOLD signal in rats, and that this effect is attenuated in almost all regions by 5-HT depletion. These findings support the use of fMRI imaging methods as a non-invasive tool to study 5-HT function in animal models, with the potential for extension to clinical studies.